A Comparative Study of Tax Systems: Real Estate Transaction Tax in the Arab Countries (Saudi Arabia, Egypt, Jordan) - Hariri, Mohammad Majdi (Journal of Economic, Administrative and Legal Sciences, 2022)
Taxes play a crucial role in the economic development of a country. The purpose of this paper is to analyse and compare the tax systems of Arab countries, as well as the role they play in the lives of our peoples. The goal of this guide is to ensure a better understanding on the Real Estate Transaction Tax (RETT) in Saudi Arabia, Egypt, and Jordan, as well as to explain the philosophy behind it in these Arab countries. Each tax system of the analysed countries is scrutinized and compared in order to create an ensemble image of the tax systems. The main results of this comparative study show that the Kingdom of Saudi Arabia is closest to the goal of realizing social justice, for which the tax systems were originally found, through the percentage obtained in all cases of the system, followed by Jordan. Secondly, Egypt is one of the countries with mostchanges in the taxsystem. Since the three countries from the Arab region and their peoples share many characteristics, this study recommends the experiment of tax coordination between Arab countries as a tool to achieve economic integration.